KEPASTIAN HUKUM TERHADAP JUSTICE COLLABORATOR DALAM PEMBERANTASAN TINDAK PIDANA KORUPSI DI INDONESIA DALAM PUTUSAN PENGADILAN TINGGI DKI JAKARTA NOMOR 5/PID.SUS-TPK/2018/PT.DKI - Yosua Hasudungan Wilbur; R. Rahaditya (Fakultas Hukum Universitas Tarumanagara, 2021)
The application of sanctions in criminal cases involves one of the offenses stipulated in the Criminal Code in which all losses and penalties for the offense are regulated, but in the case of safeguards related to the losses incurred for the offense and less than Rp. 2,500,000, it will be included in minor criminal offenses which regulate further in the Supreme Court Regulation No. 2 of 2012, but in practice many cases of theft of tipiring but other legal rules are sought in order to rule out typing as in reported cases relating to minor acts but it requires a lex specialist Act Invite Plantation to exclude tipiring. How the Problems of Trial in Light Elections Arise in Kuhp with the Housing Law in the Decision of the District Court Simalungun Number 590 / Pid.b / 2019 / PN Sim. The author uses normative legal research methods. This research is descriptive analysis. Sources of data used are primary data obtained from sources and secondary data from the results of library studies. The results of the author's research are the legal coverage of the principle of justice coverage in judging light protection cases in giving decisions considering legal aspects and proper classification of any related issues so that the legal information given can be carried out appropriately.